PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS KANTOR DINAS PENDAPATAN DAERAH PROVINSI KALIMANTAN BARAT) - B11110145, NETI KURNIANINGSIH (Jurnal Manajemen Update, 2015)
This research aimed to known the effect of work stress and job motivation on employee performance. The research was conduct at Dinas Pendapatan Daerah Provinsi Kalimantan Barat. This research was designed as an descrptive and causal. The method of data collection is conducted by questionaire and interview. The population of this research is all employee of Dinas Pendapatan Daerah Provinsi Kalimantan Barat which amounted to 90 people, and the number of samples that used is 89 people. The analysis technique used multiple linier regression analysis and equipped with validity, reliability, normality, relevant, heterokedasity test and t-test. Data is proccesed by SPSS version 21. Based on statistical test, showed that work stress have significant effect on employee performance and job motivation have significant effect on employee performance Keywords : work stress, job motivation and employee performance.